Palmitic Acid Accelerates Endothelial Cell Injury and Cardiovascular Dysfunction via Palmitoylation of PKM2 - Yu He; Senlin Li; Lujing Jiang; Kejue Wu; Shanshan Chen; Linjie Su; Cui Liu; Peiqing Liu; Wenwei Luo; Shilong Zhong; Zhuoming Li (Advanced Science)
Abstract High serum level of palmitic acid(PA) is implicated in pathogenesis of cardiovascular diseases. PA serves as the substrate for protein palmitoylation. However, it is still unknown whether palmitoylation is involved in PA‐induced cardiovascular dysfunction. Here, in clinical cohort studies of 1040 patients with coronary heart disease, high level of PA is associated with risk of major adverse cardiovascular events (MACE) and death. In ApoE−/−mice, 10 mg/kg−1 PA treatment induces blood pressure elevation, cardiac contractile dysfunction, endothelial dysfunction and atherosclerotic plaqueformation. In endothelial cells, inhibition of palmitoylation bypalmitoyl‐transferase inhibitor 2‐BP eliminates PA‐induced endothelial injury, whereas promotion of palmitoylation by depalmitoylase inhibitor ML349 exacerbates the harmful effect of PA. Palmitoyl‐proteomics analysis identifies pyruvate kinase isozyme type M2 (PKM2) as the palmitoylated protein responsible for PA‐induced endothelial injury, and Cys31 as the predominant palmitoylated site. PKM2‐C31S mutants (cysteine replaced by serine) prevents PA‐induced endothelial injury. Endothelial‐specific AAV‐C31S PKM2endo ameliorates cardiovascular dysfunction caused by PA in ApoE−/− mice. Mechanistically, PKM2‐C31 palmitoylation impairs PKM2 tetramerization to inhibit its pyruvate kinase activity and endothelial glycolysis. Finally, zDHHC13 is identified as the palmitoyl acyltransferase of PKM2. In conclusion, these findings suggest that PKM2‐C31 palmitoylation contributes to PA‐induced endothelial injury and cardiovascular dysfunction.